Centres of Excellence and Capacity Building: from Strategy to Impact. (22nd November 2017) - Hellström, Tomas
Abstract: This article reports on a Small-N study of Centre of Excellence (CoE) schemes that cover a wide variety of such schemes. The purpose is to map the ways in which strategic aims of CoE schemes relate to impacts and capacity development, and the role played by institutional arrangements such as selection, funding, evaluation, and governance in translating strategy into capacity development and other impacts. Altogether 12 CoE schemes from six countries were analysed in terms of strategy, governance, and impact or capacity building. Findings suggest that while CoE schemes tend to focus on capacity outcomes viz. network stimulation, skills development, and transfer of expertise, the most important outcome is the 'meta-capacity' involved in formulating and carrying out policy and research in new ways, developing professionalization in the academic workforce and enabling organizations such as universities to set their own priorities and engage in professional research governance.